REALITAS PEMBERLAKUAN UAN/UN - Darmaningtyas Darmaningtyas (Badan Litbang dan Diklat Kementerian Agama RI, 2007)
AbstractThough it is controversial, implementing UN as a graduation standard for any students has continued so far. Juridical bases are UU No. 20/2003 regarding National Educational System and Government Regulation (PP) No. 19/2005 regarding National Education Standard. The fact is that UN encourages students to leaarn more actively, teachers to teach better, principals to improve school quality, and parents to focus more on making their children study more enthusiastically. However, still there are parties nit agreeing with the government act. The rejection of UN is based on different interpretations on the existence of Law No. 19/2005, educational decentralization principle, different paradigm in understanding of national education objective, social reality in community, and the educational function. On the other hand, the government should fulfill minimal service standard before they implement educational nationalization.